Catalyzing Henry reactions in chloroaluminate ionic liquids - Kumar, Anil; Pawar, Sanjay S. (Journal of Molecular Catalysis A - Chemical, 2005)
Henry reactions can be accelerated in chloroaluminate room temperature ionic liquids. The choloroaluminates with higher compositions of organic species of the chloroaluminates prove to be more efficient rate promoters than the ones with lower organic species in catalyzing Henry reactions. involving both aliphatic and aromatic carbonyl compounds. The ionic liquids can be recycled five times to offer good yields. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chloroaluminates; Henry reactions; ionic liquids; Recycling

Ionic liquids as powerful solvent media for improving catalytic performance of silyl borate catalyst to promote Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Journal of Organic Chemistry, 2007)
[GRAPHICS] Use of the acidic chloroaluminate ionic liquid, including the recycled ones, can improve the catalytic activity of the toluene-coordinated silyl borate in enhancing rates, stereoselectivities, and yields of Diels-Alder reactions.

High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity